The effect of epigallocatechin 3-gallate (EGCG) on Sertoli and Leydig cells counts and spermatozoa quality of rats (Rattus norvegicus) exposed to monosodium glutamate - Sitti Az-Zahra Indira; A Ashiila Tsabita; Suherni susilowati; Sri Pantja Madyawati; Ira Sari Yudaniayanti; kusnoto kusnoto; Djoko Legowo; Nove Hidajati; Kadek Rachmawati (Universitas Airlangga, 2026)
This study aimed to determine the preventive effect of epigallocatechin 3-gallate (EGCG) on the number of Sertoli and Leydig cells in white rats (Rattus norvegicus) exposed to monosodium glutamate (MSG). This study used 25 male rats which were divided into five groups. The C– group was given only 1% Na-CMC, while the C+ group received 1% Na-CMC and 120 mg/kg BW of MSG. The T1, T2, and T3 groups were administered EGCG at doses of 4, 8, and 16 mg/kg BW, respectively, along with 120 mg/kg BW of MSG. All treatments were administered orally for 28 days. After the treatment period, the rats were sacrificed on day 29. Their testes were collected and processed into histological specimens using hematoxylin eosin (H&E) staining. The results showed that MSG exposure significantly decreased (p <0.05) the number of Sertoli and Leydig cells in the C+ group compared to the C– group. In contrast, the T1, T2, and T3 groups showed increased cell counts following EGCG administration. Epigalocathecin-3-gallate at a dose of 8 mg/kg BW showed the best potential in maintaining spermatozoa motility, viability, and plasma membrane integrity in rats exposed to MSG. EGCG, as an antioxidant, can reduce lipid peroxidation in the spermatozoa plasma membrane, thereby improving spermatozoa viability, motility, and plasma membrane integrity. In conclusion, the administration of EGCG mitigates the harmful effects of MSG on Sertoli and Leydig cell counts in white rats, with an optimal dose of 8 mg/kg BW.